2022
DOI: 10.1021/acs.energyfuels.2c02625
|View full text |Cite
|
Sign up to set email alerts
|

Viscosity and Density of Narrow Distillation Cuts from Refined Petroleum- and Synthetic-Derived Distillates in the −60 to +60 °C Range

Abstract: Aviation turbine fuel (jet fuel) must remain fluid enough for use at low temperatures typically experienced during high-altitude flights. The viscosity–temperature relationship of petroleum-derived jet fuel is described by the MacCoull correlation in ASTM D341. The maximum kinematic viscosity of jet fuel at −20 °C is regulated by specification, but for long-distance flights, viscosity of <12 mm2 s–1 at −40 °C is important. For synthesized paraffinic kerosene (SPK) to be approved as a synthetic jet fuel, compli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 48 publications
0
2
0
Order By: Relevance
“…The low temperature flow properties of FT SPK obtained from wax hydrocracking was investigated and compared to petroleum derived kerosene 40 . For the materials used in this case study, it was found that the low temperature viscosity of the FT SPK was lower than that of the petroleum derived kerosene.…”
Section: Case Studymentioning
confidence: 99%
“…The low temperature flow properties of FT SPK obtained from wax hydrocracking was investigated and compared to petroleum derived kerosene 40 . For the materials used in this case study, it was found that the low temperature viscosity of the FT SPK was lower than that of the petroleum derived kerosene.…”
Section: Case Studymentioning
confidence: 99%
“…It is worth noting however that the temperature dependence implied by Eq. 3 is significantly simpler than a variety of empirically derived relationships (Sloane and Winning, 1931;Link and de Klerk, 2022) that are more accurate over a limited temperature range, which implies that ΔE is also temperature dependent.…”
Section: Theorymentioning
confidence: 99%